(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Pair words, also known as "binomials" or "Siamese twins", are a unique English language feature. These word combinations play a crucial role in everyday speech and writing, adding depth, nuance, and expressiveness to the combination. This article explores the significance of pair words, their various types and their impact on the English language.